1981
DOI: 10.1037/0097-7403.7.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Associations to contextual stimuli as a determinant of long-term habituation.

Abstract: A series of experiments was performed to determine whether long-term habituation of the acoustic startle response in rats is mediated by conditioned associations between contextual cues and the test stimulus. Experiment 1 established parameters yielding demonstrable long-term habituation of the startle response. Experiment 2 attempted to overshadow the hypothesized associations to contextual cues by providing a more reliable predictor of the acoustic stimulus. Experiment 3 investigated the effect of changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
0
3

Year Published

1984
1984
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 43 publications
11
90
0
3
Order By: Relevance
“…However, dependency on environmental invariance is a necessary but not a sufficient condition. Indeed, views other than Wagner's theory also predict context specificity insofar as they consider the stimulus to be habituated as a complex stimulus that includes the contextual background (see, e.g., Marlin & Miller, 1981). Therefore, the following experiments were aimed at testing other predictions of the associative theory by contrasting them with those of the nonassociative view.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, dependency on environmental invariance is a necessary but not a sufficient condition. Indeed, views other than Wagner's theory also predict context specificity insofar as they consider the stimulus to be habituated as a complex stimulus that includes the contextual background (see, e.g., Marlin & Miller, 1981). Therefore, the following experiments were aimed at testing other predictions of the associative theory by contrasting them with those of the nonassociative view.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of an effect may be due to any number of reasons. For example, the environmental change may not have been discriminable by the subject (Marlin & Miller, 1981). Alternatively, the chosen parameter of the background may have been an irrelevant cue in the contextual memory (Davis & File, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies (e.g. Marlin & Miller 1981;Hall & Channell 1985;Hall & Honey 1989;Honey et al 1992) have concluded that, unlike phenomena such as latent inhibition (e.g. Kaye et al 1987) and possibly even conditioning itself (Hall & Honey 1989), habituation does appear to transfer successfully to a different test context (i.e.…”
Section: Oliver Burman and Michael Mendlmentioning
confidence: 99%